Life stressors and mental health: Depressive symptoms, anxiety, and suicidal ideation or intent during and after the COVID-19 pandemic - Shakila Meshkat; Xiaoxuan Han; Qiaowei Lin; Vanessa K. Tassone; Reinhard Janssen-Aguilar; Wendy Lou; Shauna Major; Michael Cooper; Andrew Greenshaw; Venkat Bhat (PLoS ONE, 2026)
Objective This study aimed to investigate the associations between life stressors and depressive symptoms, anxiety, and suicidal ideation or intent, while also examining how COVID-19 pandemic influenced these associations. Methods This study used data from 19,950 participants in the Mental Health Research Canada cohort. Participants who were under the age of 20 or missing data for key mental health variables were excluded from the analyses. Primary outcomes included depressive symptoms, anxiety, and suicidal ideation or intent. Their associations with life stressors (concerns about catching COVID-19, economic downturn and inflation, job loss, challenges in paying household bills, and social factors) were analyzed using logistic regressions models. Results Participants experiencing negative impacts from life stressors had significantly higher odds of having depressive symptoms (aOR: 1.46; 95% CI: 1.28–1.66), moderate to severe anxiety (aOR: 1.33; 95% CI: 1.15–1.53) and developing suicidal ideation or intent (aOR: 1.54; 95% CI: 1.36–1.74) compared to those experiencing positive impacts. The odds were higher after COVID‑19 than during COVID‑19 for depressive symptoms (aOR = 1.62 vs 1.29; p = 0.08) and moderate to severe anxiety (aOR = 1.52 vs 1.12; p = 0.03) among participants with negative impacts from life stressors. Participants who reported negative impacts from certain stressors had higher odds of adverse mental health outcomes. Challenges in paying household bills were most strongly associated with depressive symptoms (aOR: 1.96; 95% CI: 1.62–2.36), moderate to severe anxiety (aOR: 1.79; 95% CI: 1.45–2.21), and suicidal ideation or intent (aOR: 1.52; 95% CI: 1.28–1.82). Conclusions This study highlights the significant impact of life stressors on mental health, with challenges related to paying household bills being a key factor linked to depressive symptoms, anxiety, and suicidal ideation or intent. The COVID-19 pandemic exacerbated these stressors, emphasizing the need for targeted mental health interventions. Findings are subject to limitations of cross-sectional, self-reported data and unvalidated suicidality measures.